KEKERASAN VIGILANTISM DALAM TATANAN SOSIAL: SEBUAH USULAN KERANGKA ANALISIS KEKERASAN DARI KASUS AMERIKA, AFRIKA, DAN INDONESIA - Cho Youn Mee; Sjafri Sairin; Irwan Abdullah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
This article examines vigilantism as a framework to see various violence cases in Indonesia, and through which tries to open a scope for further discussion about building a scheme of violence study in general . Vigilantism is analyzed on its stance in the established socio-political order and defined as establishment violence . Various case materials from America, Africa and Indonesia are offered in this analytical framework .